Motif Individu, Karakteristik Konten Berita, dan Tingkah Laku Meneruskan Pesan Melalui WhatsApp - Selfiyani Lestari; Laras Sekarasih (Universitas Andalas, 2020)
WhatsApp is one of the most popular text-messaging mobile applications in Indonesia. Unfortunately, WhatsApp has also been found as a medium to spread false information. The current study explores what motivates individuals to forward messages on WhatsApp as well as the characteristics of information that they would forward to other users. Qualitative interviews to 20 WhatsApp users aged 19 – 78 years old were conducted to collect data. Participants reported several attributes that characterize surprising news or messages. A message is perceived as surprising if it is a breaking news or messages with unexpected or unheard information. Messages that feature events that took place with geographical proximity to them or to the person who received the forwarded messages are also considered surprising. Besides to inform friends and relatives about an event or information, participants’ responses also indicate that message forwarding serves as a conversation starter in direct messages or on WhatsApp groups. Participants’ responses indicate that forwarding surprising messages with unverified source reflect a lack of information literacy instead of a motivated or intentional act to disinform others. Keywords: News sharing, Message Forwarding, WhatsApp